Understanding the Determinants of Halal Product Purchase: A Meta-Analysis of Consumer Behavior in Muslim and Non-Muslim Contexts - Inggrida, Jedda Ayu; Adli, Danung Nur; Purnama, Septian Maulana; Mulyadi, Fadli; Sholikin, Mohammad Miftakhus; Azmi, Amirul Faiz Bin Mohd (HABITAT, 2026)
Purpose: This study aims to examine the determinants of consumer behavior in purchasing halal products by evaluating the relative influence of psychological and behavioral factors. Given the inconsistent findings reported in previous studies, this research seeks to provide a clearer understanding of the drivers of halal product consumption across different contexts. Design/Methodology/Approach: A meta-analysis was conducted by synthesizing eighteen empirical studies published between 2014 and 2024. Using a random-effects model, the study calculated Standardized Mean Differences (SMDs) for eight variables, including halal awareness, halal logo, attitude, religiosity, trust, subjective norm, purchase intention, and actual buying behavior. Publication bias was also assessed to ensure the robustness of the analysis. Findings: The results indicate that attitude (SMD = 0.331, p = 0.050) and purchase intention (SMD = 0.238, p = 0.197) are the strongest predictors of halal product purchasing behavior. In contrast, religiosity (SMD = −0.279, p = 0.030) shows a statistically significant but negative relationship, suggesting that religious commitment alone may not sufficiently explain consumer behavior without contextual enablers such as certification trust, accessibility, and product availability. Meanwhile, halal logo and consumer awareness demonstrate smaller and more heterogeneous effects across studies. Originality/Value/Novelty: This study contributes to the literature by providing a quantitative synthesis of factors shaping halal product purchasing behavior through meta-analysis. The findings highlight the importance of integrating psychological determinants, particularly attitude and purchase intention, with contextual market factors to better understand consumer behavior in halal markets.